A green route for the synthesis of novel optically active poly(amide–imide) nanocomposites containing N-trimellitylimido-l-phenylalanine segments and modified alumina nanoparticles. (June 2014) - Mallakpour, Shadpour; Khadem, Elham
In the present study, novel optically active poly(amide–imide)/alumina nanocomposites (PAI/Al2 O3 NCs) containing different amounts of modified α-Al2 O3 nanoparticles (NPs) were synthesized using the ultrasonic-assisted technique. To improve NPs dispersion and increase the possible interaction between NPs and PAI matrix, the surface of α-Al2 O3 NP was modified with bioactive diacid coupling agent. The PAI chains were formed from the polycondensation of N -trimellitylimido-l -phenylalanine diacid with 1, 5-diamino naphthalene under green conditions. The obtained polymer and inorganic metal oxide NPs were used to prepare chiral PAI/Al2 O3 NCs through the ultrasonic irradiation. PAI/Al2 O3 NCs were characterized by Fourier transform infrared spectra, x-ray diffraction patterns, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and ultraviolet–visible (UV-Vis). TGA results confirmed that the heat stability of the prepared NP-reinforced composites was improved compared with the pure polymer. In addition, TEM and FESEM images showed that NPs were dispersed into the polymer matrix at nanoscale.